Functional materials for sustainable energy applications - Kilner, John A. (Woodhead Publishing in energy ;, 2012)
Global demand for low cost, efficient and sustainable energy production is ever increasing. Driven by recent discoveries and innovation in the science and technology of materials, applications based on functional materials are becoming increasingly important. Functional materials for sustainable energy applications provides an essential guide to the development and application of these materials in sustainable energy production. Part one reviews functional materials for solar power, including silicon-based, thin-film, and dye sensitized photovoltaic solar cells, thermophotovoltaic device modelling and photoelectrochemical cells. Part two focuses on functional materials for hydrogen production and storage. Functional materials for fuel cells are then explored in part three where developments in membranes, catalysts and membrane electrode assemblies for polymer electrolyte and direct methanol fuel cells are discussed, alongside electrolytes and ion conductors, novel cathodes, anodes, thin films and proton conductors for solid oxide fuel cells. Part four considers functional materials for demand reduction and energy storage, before the book concludes in part five with an investigation into computer simulation studies of functional materials. With its distinguished editors and international team of expert contributors, Functional materials for sustainable energy applications is an indispensable tool for anyone involved in the research, development, manufacture and application of materials for sustainable energy production, including materials engineers, scientists and academics in the rapidly developing, interdisciplinary field of sustainable energy. An essential guide to the development and application of functional materials in sustainable energy productionReviews functional materials for solar powerFocuses on functional materials for hydrogen production and storage, fuel cells, demand reduction and energy storage.